Pengaruh Strategi Everyone is a Teacher Here Berbantuan Spinning Wheel terhadap Minat Belajar Siswa pada Pembelajaran Pendidikan Pancasila - Amalia, Dhea; Prihartiningtyas, Nindy Citroresmi; Sumarli, Sumarli (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to: (1) describe the difference in students' learning interests between classroom learning using the everyone is a teacher here strategy assisted by spinning wheels and classroom learning using direct learning; (2) describe the magnitude of the influence of the Everyone is a Teacher Here learning strategy on interest student learning in Pancasila education learning; (3) describe the students' response to the implementation of the Everyone is a Teacher Here strategy assisted by a spinning wheel in Pancasila Education learning. This research used is quantitative or experimental research. The population in this study were students in classes VA and VB with 30 students. The sampling technique is total sampling / saturated sampling technique, the sample in this study were students in classes VA and VB at SDN 24 Singkawang, totaling 30 students. The data collection technique in this research is in the form of an adapted student learning interest questionnaire from Trisna (2021) and an adapted student response questionnaire from Timara (2021). The data analysis technique is demonstrated by carrying out a t test on the first problem formulation, an effect size test on the second problem formulation and carrying out descriptive percentages on the third problem formulation. The results of the research show that (1) there are differences in students' learning interest between classes with the everyone is a teacher here learning strategy assisted by spinning wheel media and direct classes, (2) the influence of the everyone is a teacher here strategy assisted by spinning wheel media on students' learning interest is in the medium category, and (3) positive student responses to the implementation of the everyone is a teacher here strategy assisted by spinning wheel media on students' interest in learning in Pancasila Education.